Patterns of molecular evolution at the amylase locus in Drosophila. - Abukashawa, Sumaia. (University of Ottawa (Canada), 1990)
Genes encoding the starch-degrading enzyme, alpha-amylase, are found in all major groups of animals, plants and microbes. In this thesis, amylase-coding sequences have been chosen as a model system to investigate the patterns of molecular evolution in an enzyme-coding gene. Previous phylogenetic comparisons of amylase-coding sequences have shown high levels of primary sequence conservation over long evolutionary periods. The studies described here have concentrated on the evolution of these genes within the genus Drosophila. I have studied patterns of genetic variation within populations of a single species, Drosophila melanogaster, using two techniques: (i) allozyme variation and (ii) restriction fragment length polymorphisms (RFLPs). In order to get more precise information on the intraspecific patterns of variation, I have also isolated and partially sequenced the amylase genes from a wildtype strain of D. melanogaster. This sequence was compared to the known sequences which have already been described for laboratory strains. The work was extended to interspecific comparisons by studying amylase sequences from species that were closely-related to D. melanogaster (in this case D. erecta), and also a distantly-related species (D. virilis). This involved the isolation and sequencing of the amylase gene from a D. virilis genomic library. The results revealed several interesting patterns in the evolution of: (i) the primary gene sequences (e.g., gene conversion and codon bias), (ii) gene structure (e.g., changes in intron frequency and location) and (iii) gene organization (e.g., variation in the number of gene copies). These results, concerning both short-term and long-term patterns of molecular evolution within the genus Drosophila, are discussed in the context of what is currently known about patterns of molecular evolution in general, and about the molecular evolution of amylases in particular.
Keywords: Biology, Genetics.